SAE Technical Paper Series 2010
DOI: 10.4271/2010-01-2247
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Microscopic Imaging of the Initial Stage of Diesel Spray Formation and Primary Breakup

Abstract: The formation and breakup of diesel sprays was investigated experimentally on a common rail diesel injector using a long range microscope. The objectives were to further the fundamental understanding of the processes involved in the initial stage of diesel spray formation.Tests were conducted at atmospheric conditions and on a rapid compression machine with motored in-cylinder peak pressures up to 8 MPa, and injection pressures up to 160 MPa. The light source and long range imaging optics were optimised to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…However, the energy output of high-power LEDs is still insufficient to enable blur-free microscopic imaging of high-speed sprays. The challenging lighting requirements for such experiments has limited their application to atmospheric conditions, with the exception of our preliminary studies [16][17][18][19], and the recent work of Manin et al [20]. Additional complications introduced in high pressure and temperature environments include the presence of turbulence, density and temperature gradients in the gas phase, which will result in refractive index fluctuations.…”
Section: Introductionmentioning
confidence: 97%
“…However, the energy output of high-power LEDs is still insufficient to enable blur-free microscopic imaging of high-speed sprays. The challenging lighting requirements for such experiments has limited their application to atmospheric conditions, with the exception of our preliminary studies [16][17][18][19], and the recent work of Manin et al [20]. Additional complications introduced in high pressure and temperature environments include the presence of turbulence, density and temperature gradients in the gas phase, which will result in refractive index fluctuations.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies [21][22] have revealed thought that the TAB model can produce excessive droplet breakup that is not in agreement with experimental data. This is attributed to the fact that cavitation and turbulence phenomena inside the injector nozzle and liquid core, experimentally shown to be of great importance to atomization [23][24][25], as well as non-linear droplet distortion effects are not accounted for in the TAB model. In the WAVE model [26][27], derived from a linear stability analysis of liquid jets, the breakup time is determined by surface instability of droplets as a function of the wavelength and the frequency of the Kelvin-Helmholtz wave.…”
Section: Introductionmentioning
confidence: 88%
“…The injected high pressure diesel sprays go through different temporal stages that can be broadly classified into four regimes. The first regime is the start of injection (SOI), where a 'mushroom head' forms as fuel leaves the nozzle because of the residual fuel in the nozzle sac [3]. The transient regime follows, which covers from the SOI to the time instant at which the needle inside the nozzle reaches a fully open position.…”
Section: Introductionmentioning
confidence: 99%